(untitled) (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-1-104-115 Abstract. The theatrical code is considered as a way of representing German history in Uwe Timm’s novel «Halbschatten». The manifestations of theatricality in the novel chronotope, the organization of artistic discourse, and the system of images are studied. The fragmentary nature of the novel composition realizes the author’s perception of history as a trauma, which is opposed by the search for integrity that arises at the level of the artistic image. The action of the novel implicates the image of history as a theater of shadows. The action of the novel is considered as an allegory of the creative process, the conclusion about the polygenre nature of Timm’s novel as a historical novel and a metanovel is substantiated. Key words: Uwe Timm, Halbschatten, historical novel, metanovel, German literature, theatricality, narrative dramatization, postmodernism